Potensi Mikroalga Anabaena sp. Sebagai Bahan Utama Bioetanol - Imam Mishbach; Nila Suci Permatasari; M Zainuri; Hermin Pancasakti Kusumaningrum; Endah Dwi Hastuti (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2022)
Bioethanol is an energy source that can be used to reduce the use of fossil fuels. It has some advantages such as biodegradable, and non-toxic because the main ingredients come from biomass and produce fewer pollutants. Anabaena sp. is Cyanobacteria that can be used as the main ingredient of bioethanol, its advantages are that it does not compete with food, its growth is fast and it contains carbohydrates. The purpose of this study was to analyze the carbohydrate content of Anabaena sp. The stages of the research carried out were Anabaena sp. cultivated for 30 days in freshwater using Walne media, then harvested. The collected biomass was then tested using proximate analysis with two replications. In this study, the data obtained in the form of growth of Anabaena sp. and carbohydrate content was presented in the form of tables and graphs. The results showed that Anabaena sp. which was cultivated for 30 days and harvested biomass was carried out in an exponential phase (day 14), had a carbohydrate content of 25.43 %, protein of 53.70 %, and lipid of 2.40 %. Based on the results of the study, it can be concluded that the biomass of Anabaena sp. has a carbohydrate content of 25.43 % and has the potential as the main ingredient of bioethanol.